The relationship between the bunkie-test and selected biomotor abilities in elite-level rugby players - Van Pletzen, D. (University Stellenbosch, 2010)
The purpose of this exploratory study was to assess the fascia alignment in kinetic muscle chains and to determine the relationship between these results and selected biomotor abilities in rugby players. It is suggested that restrictions in the fascia along the kinetic chains inhibit muscle function and therefore influence movement patterns, such as those required by skilled rugby players. The isometric Bunkie-test was used to assess fascia alignment in ten kinetic chains related to movement patterns. Standard functional tests were used to assess agility, speed, speed endurance, lower body explosive power and upper body muscle endurance. The relationship between fascia alignment and injury occurrence was also determined. The subjects (n = 121) were all elite-level rugby players from three rugby academies. They participated voluntarily in a once-off assessment, consisting of the Bunkie-test, an Illinois agility test, a 10m sprint test, a 40m sprint test, a repeated sprint test, a vertical jump test and a maximum pull-ups test. Subjects also completed an injury questionnaire regarding all previous and current injuries. No intervention was applied and the statistical analysis was based on this assessment. Numerous significant relationships (p < 0.05) were found between the results of the Bunkietest and results of the performance tests. Players performing better on the Bunkie-test demonstrated better biomotor abilities. Very few significant findings (p < 0.05) were found when comparing the results of the Bunkie-test to injury occurrence. The conclusion was made that restrictions in the fascia of kinetic chains, as determined by the Bunkie-test, could influence a rugby player`s ability to perform biomotor movements optimally. Whether restrictions in the fascia resulted in an increased injury occurrence could not be shown. The Bunkie-test might be a tool for coaches and rehabilitation therapists to identify weaknesses and imbalances in the kinetic chains of athletes. Addressing these problems could then lead to improvements in sport performance.